(3OQQ GdSdhc ajef Mce eUQ ef GdfhGH hGdedhcs - (3GdfLGQj , eMeO YGbd Hf eMeO cGTas
(3ChdgG (B:s
(3CeG HYO gPG OaJQ hLjR egOJg JhWFI GdJGQjN GdPi CfG HUOOg LeYJ ajg ef SCJcde Ydjg ef edhc eUQ hfhGMjgG s
(3BNQgG (B:s
(3CafOjfG GdCYXe ESeGYjd HGTG s
(3gfGc Tc aj Cf fGSN GdeNWhWI gh GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B116s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B170 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs